Curcumin Inhibits Papillary Thyroid Cancer Cell Proliferation by Regulating lncRNA LINC00691 - Zhihua Li; Youbing Gao; Lijun Li; Shanshan Xie (Analytical Cellular Pathology)
Papillary thyroid cancer (PTC) is a type of epithelial-derived differentiated TC that reportedly accounts for a majority of TCs. Curcumin, a polyphenolic compound and a member of the Zingiberaceae (ginger) family derived from turmeric plants, can exhibit anticancer effects. Herein, we aimed to investigate the effect of curcumin on PTC and elucidate underlying mechanisms. Accordingly, PTC B-CPAP cells were treated with curcumin, in combination with/without long noncoding RNA LINC00691 inhibition, to determine the effect of curcumin and its relationship with LINC00691 in PTC cells. We observed that curcumin treatment decreased B-CPAP cell proliferation and promoted apoptosis. Curcumin inhibited LINC00691 expression in B-CPAP cells. Curcumin administration or si-LINC00691 transfection alone promoted ATP levels, inhibited glucose uptake and lactic acid levels, and inhibited lactate dehydrogenase A and hexokinase 2 protein expression in B-CPAP cells, which were further enhanced by combination treatment. Moreover, curcumin administration or si-LINC00691 transfection alone inhibited p-Akt activity, further suppressed by combination treatment. Akt inhibition promoted apoptosis and suppressed the Warburg effect in B-CPAP cells. In conclusion, our findings indicate that curcumin promotes apoptosis and suppresses proliferation and the Warburg effect by inhibiting LINC00691 in B-CPAP cells. The precise molecular mechanism might be mediated through the Akt signaling pathway, providing a theoretical basis for the treatment of PTC with curcumin.